2013
DOI: 10.2527/jas.2012-5733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variability in lighting and temperature environments for mature gilts housed in gestation crates on measures of reproduction and animal well-being1

Abstract: The effects of room temperature and light intensity before breeding and into early gestation were evaluated on the reproductive performance and well-being of gilts housed individually in crates. In eight replicates, estrus was synchronized in mature gilts (n = 198) and after last feeding of Matrix were randomly assigned to a room temperature of 15°C (COLD), 21°C (NEUTRAL), or 30°C (HOT) and a light intensity of 11 (DIM) or 433 (BRIGHT) lx. Estrous detection was performed daily and gilts inseminated twice. Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 49 publications
2
20
2
Order By: Relevance
“…Consistent with studies in cattle (Bernardini et al, 2012), sheep (Miranda-de la Lama et al, 2010, and pigs (Canaday et al, 2013), cortisol concentrations in rabbits were lowest in summer. Seasonal variation in immune responses has also been described in several species (reviewed by Nelson and Drazen, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with studies in cattle (Bernardini et al, 2012), sheep (Miranda-de la Lama et al, 2010, and pigs (Canaday et al, 2013), cortisol concentrations in rabbits were lowest in summer. Seasonal variation in immune responses has also been described in several species (reviewed by Nelson and Drazen, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, in the present experiment, no difference between groups were observed for the number of feeder visits and time standing at the feeder during the observation period before farrowing. These behaviors have been described as indicators of heat discomfort caused by high ambient temperatures (De Oliveira Júnior et al, 2011;Canaday et al, 2013). The number of postural changes, which is considered to increase as a general response to stress in sows (Jarvis et al, 1999), also did not increase in the present experiment.…”
Section: Discussioncontrasting
confidence: 45%
“…This modification of sow postural behavior was the only behavior strategy to adapt to the high ambient temperature observed in our study. Canaday et al (2013), although working with mature nonlactating gilts, also found that animals kept in crates in a hot environment (30°C) spent a higher proportion of time lying laterally, whereas gilts kept in crates in neutral and cold environments spent more time lying in the ventral position. Nonetheless, Canaday et al (2013) also observed that gilts in a hot environment reduced the proportion of time spent in a standing position, as did Renaudeau et al (2003), who studied sows kept at 28°C between d 8 and 14 of lactation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…When comparing a thermoneutral environment of 20°C to a heat stress environment of 28°C over a 6 days period, lactating sows have been observed to reduce standing and sitting postures from 18 to 11.6% of time ( 43 , 48 ) and correspondingly increase lying postures, especially lying laterally ( 9 ). Moreover, non-lactating gilts maintained for 30 days in a hot environment of 30°C spent also more time lying laterally than lying sternally in comparison with neutral (21°C) and cold environments (15°C) ( 48 ). Lying laterally appears to be a strategical posture when pigs suffer from a heat stress.…”
Section: Discussionmentioning
confidence: 99%